The management perspective of the prophetic leadership model - Fontaine, Rodrigue Ancelot Harvey; Ahmad, Khaliq; Oziev, Gapur (Institute of Social Sciences & Development, Pakistan, 2020)
Management is more than a century old discipline that has evolved in the form of organizational theories and management thoughts. Principles of management based on teachings of Islam have proved themselves successful in the shiny history of sīrah and pious caliphs. This study proposes an Islamic perspective of management and leadership thinking that is tied to the conventional theory of management. It is intended to integrate the approach of current system with the Islamic perspective of management and leadership with the focus on human-resource-development aspects of the prophetic leadership. The article purposes a management model namely the Prophetic Leadership Model (PLM) discussing the key management activity mentioned in the Qur’ān namely shurā (consultation). The study elaborates the significance of: the understanding of the Qur’ān and the Sunnah, having a growth mind-set and a working knowledge of the systems school of management theory, besides conventional leadership skills, in effectively adapting the PLM. The model is validated by using events from the life of the Prophet (peace be upon him) and is shown, with the help of a case study, to be applicable in current management practices provided all the necessary leadership characteristics are developed through training and development programs.